Heat stress of two tropical seagrass species during low tides – impact on underwater net photosynthesis, dark respiration and diel in situ internal aeration. Issue 4 (23rd February 2016) - Pedersen, Ole; Colmer, Timothy D.; Borum, Jens; Zavala‐Perez, Andrea; Kendrick, Gary A.
Summary: Seagrasses grow submerged in aerated seawater but often in low O2 sediments. Elevated temperatures and low O2 are stress factors. Internal aeration was measured in two tropical seagrasses, Thalassia hemprichii and Enhalus acoroides, growing with extreme tides and diel temperature amplitudes. Temperature effects on net photosynthesis ( P N ) and dark respiration ( R D ) of leaves were evaluated. Daytime low tide was characterized by high p O2 (54 kPa), pH (8.8) and temperature (38°C) in shallow pools. As P N was maximum at 33°C (9.1 and 7.2 μmol O2 m −2 s −1 in T. hemprichii and E. acoroides, respectively), the high temperatures and reduced CO2 would have diminished P N, whereas R D increased (Q10 of 2.0–2.7) above that at 33°C (0.45 and 0.33 μmol O2 m −2 s −1, respectively). During night‐time low tides, O2 declined resulting in shoot base anoxia in both species, but incoming water containing c . 20 kPa O2 relieved the anoxia. Shoots exposed to 40°C for 4 h showed recovery of P N and R D, whereas 45°C resulted in leaf damage. These seagrasses are 'living near the edge', tolerant of current diel O2 and temperature extremes, but if temperatures rise both species may be threatened in this habitat.